Sosialisasi Peran Paralegal Dalam Meningkatkan Pengetahuan Warga Desa Cilame Di Bidang Hukum - Musa Darwin Pane; Sahat Maruli Tua Situmeang; Akmal Alfarizzi (LPPM Universitas Pamulang, 2023)
Community service activities through the theme of socializing the role of paralegals in increasing the knowledge of Cilame villagers in the field of law are an effort to mitigate law enforcement against potential law violations that occur in the community as a social phenomenon. In carrying out this community service, student involvement is very important considering that students as agents of change are expected to help implement legal rules. In addition, students are expected to be able to increase solidarity and concern for increasing legal awareness in society. While the results achieved in this service program are increasing legal awareness through increasing knowledge of Cilame Village residents in the field of law, especially the importance of the role of legal persons through socialization activities using lecture mechanisms, discussions. This activity is carried out so that the community understands and knows the importance of the role of paralegals. The role of paralegals is very important in fulfilling access to justice for the community, especially the poor and other vulnerable groups. In addition to preparing people who are aware of the law, paralegals also provide human rights protection to people who are dealing with the law. The results of the service program are shown by the formation of a paralegal community, increased awareness, and public knowledge of their rights in the legal field. To realize the program for establishing the role of paralegals in Cilame Village, the role of the Cilame Village government is very important, this is based on the fact that the institution is the driving force behind the progress of a village. The village government is at the forefront of dealing directly with the people who run and oversee government programs in general. Judging from the potential for increasing legal awareness, Cilame Village is quite potential for the formation of paralegals. Through this service activity, it is seen that there is an increase in public understanding of the importance of legal for the community as a form of sustainable fulfillment of human rights. During the implementation of community service activities in Cilame village it went well and got enthusiasm.